The Role of Online Teaching Among the Undergraduate Dental Students During the Current COVID-19 Pandemic in India: A Pilot Study - Sonu Acharya; Tharian B. Ematty; Sheetal Acharya (Association of Support to Oral Health Research (APESB), 2021)
Objective: To assess the usefulness of online teaching for undergraduate students during this Corona pandemic, to point the drawbacks of online teaching, and to learn the areas of improvement in online teaching for the future. Material and Methods: A descriptive cross-sectional study on 130 students was done in Bhubaneswar, Odisha, India. The questionnaire consisted of two parts, personal details and specific information. The first part of the questionnaire consisted of questions related to age, gender, etc. The second part had questions pertaining to online teaching. Pearson's Chi-square test was applied and the level of significance was set at 5%. Results: Most of the students (83.3%) were in the view that classroom lectures are the best mean of imparting knowledge, which was significant (p<0.001). A significant number of students (88.1%) agreed that online teaching is the best method of teaching apart from classroom teaching. Almost all the students (93%) agreed significantly that online teaching is the best way to learn in this present pandemic scenario. Most students (59.6%) agreed that connectivity/network issue is a major drawback in online teaching, which is again significant (p<0.001). Conclusion: Here in these testing times, the role of online teaching becomes important for medical/dental students, both undergraduates and postgraduates, to keep up with their studies.